Sonification of geometry - Ma, Chunyou (Nanyang Technological University, 2024)
Because of the incredible information gathering and dissemination capabilities, the Internet has brought tremendous convenience to modern life. People can easily receive massive amounts of information from their headphones. More people realize that “visual sense is already highly loaded” [1]. One way to solve it is to make use of auditory sense. The aim of this project is to develop a series of Unity scripts that bridge the gap between geometry and audio. These scripts are designed to calculate the cross-sectional area of various geometric objects and subsequently generate audio clips based on these calculations. The unique aspect of this endeavor lies in its ability to translate the physical properties of geometric shapes into auditory experiences. Users can listen to these audio outputs to gain an approximate understanding of the characteristics of different geometric objects. This innovative approach not only allows for a novel means of perceiving and differentiating between geometrical properties but also enhances the accessibility of geometric concepts through auditory learning.